A framework for Performance Management Practices in the Precast manufacturing Industries in Chhattisgarh (International Journal of Food and Nutritional Sciences, 2022)
Rapid urbanization in India requires significant infrastructure. In the present scenario due to architectural innovation in the construction industries, precast technology is fast adopting itself. Architects and structural engineers now have alternative solutions to meet more demanding building criteria, especially in terms of total cost efficiency, high quality of works and more environmental friendly projects. But for a developing country like India, the productivity and quality of construction needs improvement along with considering the safety of workers into account. This paper highlights the study for adoption of Precast Technology for cost-effective construction in Indian Scenario.